If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(v+1)+8v=2(v-3)
We move all terms to the left:
6(v+1)+8v-(2(v-3))=0
We add all the numbers together, and all the variables
8v+6(v+1)-(2(v-3))=0
We multiply parentheses
8v+6v-(2(v-3))+6=0
We calculate terms in parentheses: -(2(v-3)), so:We add all the numbers together, and all the variables
2(v-3)
We multiply parentheses
2v-6
Back to the equation:
-(2v-6)
14v-(2v-6)+6=0
We get rid of parentheses
14v-2v+6+6=0
We add all the numbers together, and all the variables
12v+12=0
We move all terms containing v to the left, all other terms to the right
12v=-12
v=-12/12
v=-1
| −13m=−156 | | 6+x2=42 | | -6(v-1)=-4v-10 | | 7x+4=-60 | | −8x2=−15x+2 | | (x)=x^2+4x+4 | | 30;5x+7=107 | | y^2+5y-1050=0 | | 3(w+7)-5w=23 | | 8(x+3)=7(4) | | 5/2-2/y=7 | | 8b-4b=32 | | 0.45x=0.009 | | -10;7(y-1)=63 | | 4k+k=35 | | h4=15 | | 0.45x=0.0009 | | –2.73=–0.42r | | 0=-5t+3-t-4+8t | | 6n+2n=48 | | -|-x|=-12 | | 2x+8+3x+2=25 | | 30;x/6=5 | | 4=10b | | -19=m+9 | | 3(4x+1)=16x+1-4x+2 | | -9x-13=-90 | | 52+14m=276 | | 20x-8=5(4x+8) | | 9n-6=6 | | 10x+36=x | | (y+6)=180 |